Exchange Rate Management in Advanced Transition Economics - Grubacic, Sanja (2017)
The purpose of my sabbatical leave was to enable me to engage in writing a manuscript on Exchange Rate management in Advanced Transition Economics. This project involved gathering, analyzing, and preparing for publishing the new empirical evidence on behavior of exchange rates in several economies of East and Central Europe. The analysis intended to contribute to a theoretical and empirical literature on the importance of foreign exchange markets and exchange rate management in promoting a country's internal and external balance.
Keywords: dept.eco; faculty_collection; sabbatical_report

Stale economic news, media and the stock market - Birz, Gene (Journal of Economic Psychology, 2017)
I employ a classification of headlines from newspapers and wire services to examine whether stale macroeconomic news affects stock prices. Unlike with individual stocks, the cost of obtaining information about major economic releases is relatively low. Thus, stock prices should adjust to economic news announcements prior to their coverage in newspapers. I find statistically and economically significant relationship between stale news stories on unemployment and next week's S&P 500 returns. This effect is then completely reversed during the following week. These findings show that investors are affected by salient information and support the hypothesis that investors overreact to stale macroeconomic news reported in newspapers. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Attention; Efficient markets; Macroeconomic announcements; Media; Salience; dept.eco; dept.fin

Classical literature gives life to business paradox and systems integration - Page, Robert; Andoh, Samuel; Smith, Robert (Administrative Issues Journal Education Practice and Research, 2017)
Keywords: dept.eco; dept.mgt

An investigation into the sensitivity of money demand to interest rates in the Philippines - Patalinghug, Jason C. (Journal of Applied Business and Economics, 2017)
A scholarly article by author Jason C. Patalinghug, published in the Journal of Applied Business and Economics
Keywords: dept.eco; ⛔ No DOI found

Examining the dynamic linkages of performance and volatility of REIT returns - Dania, Akash; Dutta, Sandip (The Journal of Wealth Management, 2017)
This article extends the literature on the financial performance of real estate investment trusts (REITs) by examining whether U.S. REIT returns are impacted by global REITs and other real estate subsectors, such as the U.S. Real Estate Index (USRE) and the U.S. Mortgage Finance Index (USMF). The authors also explore the issue of volatility transmission and the asymmetric effect of volatility spillover on U.S. REIT returns from innovations originating in other real estate subsectors and Global REITs. Results suggest that U.S. REITs are impacted by USRE and USMF returns. There is also evidence of volatility spillover from key real estate constituents-that is, USRE and USFM returns and global REIT markets. These results can be attributed to the changing dynamics of the real estate sector and the gradual integration of the global real estate sector as an asset class. These findings have strong implications for constructing global portfolios including REITs.
Keywords: dept.eco; dept.fin

Broadband internet and new firm location decisions in rural areas - Kim, Younjun; Orazem, Peter F. (American Journal of Agricultural Economics, 2017)
Keywords: dept.eco; peer-reviewed

Universal demographic data collection standardization for better decision-making - Yahav, Lara; Thorson, James (American Journal of Management, 2017)
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Comparison of Single-Payer and Non Single-Payer Health Care Systems: A Study of Health Administration Efficiency - Yu, Jia; Zhang, Yi (Modern Economy, 2017)
The United States spends nearly twice as much per capita on health care as several OECD countries. Based on previous research, universal health care decreases the total health care expenditure due to the single-payer system; it is still unknown whether a mixed health care system has superiority. In this study, we compare and evaluate both quality of care and administrative costs among six developed countries, upon three groups: single-payer universal health care system (Australia and Canada), two-tier health care system (France and Japan), and insurance mandate health care system (Switzerland and the US). The results show that both single-payer system and two-tier system are superior to insurance mandate system on health insurance administration costs. Also, regarding insurance mandate system, the healthcare system in Switzerland is more efficient than that in the US. So, we conclude that it is possible for the US to choose a diverse healthcare system, instead of focusing on one system, to trim the healthcare administration cost and improve the quality of care for the entire country.
Keywords: dept.eco

A comparative analysis of Ethiopian and Ghanaian women entrepreneurs - Thorson, James; Gebremariam, Yilma; Andoh, Samuel K. (International Journal of Interdisciplinary Research, 2017)
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found